Supervivencia y crecimiento de encina ALCORNOQUE (Quercus suber) UTILIZANDO SEIS TIPOS DE TUBOS INVERNADERO - NAVARRO CERRILLO, R M; MARTÍNEZ SUÁREZ, A (II Congreso Forestal Español, 1997)
Achieving acceptable survival and growth of oak species on afforestation practices has been difficult. Several alternatives to improve establishment have been proposed, seeing that treesshelters are one of the most effective protection in improving survival and initial growth. Six kinds of treeshelters to improve establisment of Quercus ilex and Quercus suber were investigated
Keywords: Afforestation; Q.suber; Quercus ilex; Treeshelters